The Optimization of Human Resource’s Performance in Islamic Microfinance Institutions Through Job Analysis and Competency Model - ismail, verni yuliaty; Zain, Efendy; Zulihar, . (School of Business and Management Institut Teknologi Bandung, 2015)
Abstract. This study aims to develop a standard job analysis and human resource competency model for Islamic Micro Finance Institutions (Baitul Maal wat Tamwil), so it could be a reference for others, providing a standard professional human resources management on MFIs. This research is a field study designed as a survey, through the method of interviewing job holders and the supervisor with direct observation of the activities of field staffs. The data was analysed in the form of a verbal description of qualitative data. The main activity of the staff of MFIs is to encourage the low economic community through the activities of saving and financing. MFIs main characteristic is the principle of being directly in the field thus forming networks through regular meetings and maintaining a reliable service. MFIs personnel competency model consists of a cluster model based on teamwork/collaboration, customer focus, and communication competencies; technical cluster includes technical expertise and managing work competencies; and personal cluster is integrity, achievement orientation, and self-control competencies.Keywords: Baitul Mal Wattamwi, competency model, job description, job specification, micro finance institution